The development of meta-competencies in undergraduate students using personality development theory - Vasiljeva, Marina Vladimirovna; Alan Kanamatovich Karaev, Marina Ivanovna Ivleva, Yuriy Grigoryevich Volkov,; Marina Ivanovna Podzorova, Natalya Ivanovna Nikitina, (Opción, 2019)
The purpose of this research is to determine the successful stages of competence development of students in the higher education system through the lens of the personal development theory. A qualitative assessment of the development of the students’ professional competencies was carried out in accordance with Bloom’s taxonomy of educational objectives. It was demonstrated that 70 % of the changes in the development levels of the professional competencies were conditioned by the meta-competency levels and 30 % by other factors. In conclusion, the development of meta-competencies determines the choice of actual development trajectory as the ability to translate an immense potentiality into reality.